Efforts to Improve Mastery of Arabic Vocabulary Through the Application of Demonstration and Association Techniques for Class XI Students of SMA 3 Muhammadiyah Padang - Ritonga, Dahlan Hatoguan (Universitas Muhammadiyah Sumatera Barat, 2025)
Mastery of vocabulary (mufradat) is a fundamental foundation in learning the Arabic language. However, eleventh-grade students at SMA 3 Muhammadiyah Padang often encounter difficulties in memorizing and contextually using new vocabulary, resulting in low motivation and language competence. This study aims to investigate the application of demonstration and association techniques as an innovative solution to address this problem. The research employs a qualitative approach with a case study method. Data were collected through participant observation, in-depth interviews with teachers and students, and document analysis. The results indicate that the implementation of the demonstration technique, where students physically enact the meaning of vocabulary, successfully created a concrete learning experience and facilitated understanding. Meanwhile, the association technique, which links new words to images, stories, or students' personal experiences, was effective in strengthening long-term memory. The combination of these two techniques not only significantly enhanced vocabulary retention but also fostered an active, creative, and enjoyable learning environment. Students became more confident and enthusiastic in using the learned vocabulary in simple sentences. It is concluded that the integration of demonstration and association techniques is a potential and effective strategy for improving the mastery of Arabic mufradat at the secondary school level.